Artificial Intelligence in Translation: Benefits and Drawbacks - Saitkhanova Aziza (Scientific Trends, 2024)
This study examines the role of artificial intelligence (AI) in translation, where the growing need for multilingual communication intersects with the challenges posed by a unique linguistic and cultural context. With Uzbek as the primary language and Russian as a widely used secondary language, AI-driven translation tools are increasingly adopted across various sectors, including government, education, and business. This paper explores the advantages, such as efficiency and accessibility, and the disadvantages, such as lack of cultural nuance and limited data on Uzbek. The research highlights the importance of localizing AI tools and proposes solutions for overcoming existing challenges.
Keywords: Artificial Intelligence, Translation, Uzbek Language, Localization, Cultural Sensitivity, Neural Machine Translation, Natural Language Processing, Uzbekistan, Multilingual Communication, Language Technology, Digital Transformation, National Corpus of Uzbek Language.